2015
DOI: 10.5028/jatm.v7i3.471
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization and Applications of Iron Oxide Nanoparticles - a Short Review

Abstract: Iron oxide is a mineral compound that shows different polymorphic forms, including hematite (α-Fe 2 O 3 ), magnetite (Fe 3 O 4 ) and maghemite (γ-Fe 2 O 3 ). Solid propulsion technology nanoparticulate materials, such as hematite and maghemite, exhibit high performance on thermal decomposition of ammonium perchlorate. The enhanced catalytic effect of metallic iron oxide nanoparticles is attributed to their particle size, more active sites and high surface area, which promotes more gas adsorption during thermal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
100
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(107 citation statements)
references
References 28 publications
3
100
0
Order By: Relevance
“…Nanotechnology is a technology to manipulate matter through some chemical and/or physical processes to produce nanostructured materials with novel properties and functions [1]. In recent years, nanostructured materials are attracting great interest in different fields such as research and development [2], biomedical [3], storage media [4], and environmental remediation [5]. The properties that empower the application of nanomaterials in those fields are their sizes (diameter range between 1-100 nanometers) [6], magnetic properties [7], and catalytic properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology is a technology to manipulate matter through some chemical and/or physical processes to produce nanostructured materials with novel properties and functions [1]. In recent years, nanostructured materials are attracting great interest in different fields such as research and development [2], biomedical [3], storage media [4], and environmental remediation [5]. The properties that empower the application of nanomaterials in those fields are their sizes (diameter range between 1-100 nanometers) [6], magnetic properties [7], and catalytic properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…These advantages support their utilization in pharmaceutical applications, and getting suitable drug release control on the target tissues could be beneficial in several clinical situations, such as infections, inflammations, and cancer. However, more toxicological clinical investigations about IOMNPs are necessary.Since the early 1960s, metal oxides were used for magnetic separations [3,16]. Specifically, nanoparticles composed of iron oxide attracted great interest for pharmaceutical applications [1,[3][4][5][6]11,12,17,18].…”
mentioning
confidence: 99%
“…However, more toxicological clinical investigations about IOMNPs are necessary.Since the early 1960s, metal oxides were used for magnetic separations [3,16]. Specifically, nanoparticles composed of iron oxide attracted great interest for pharmaceutical applications [1,[3][4][5][6]11,12,17,18]. This mineral compound shows different polymorphic forms, such as hematite, magnetite, and maghemite [19].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of their large size compared to inorganic salts and organic compounds, it is not easy to generate significant osmotic pressure using magnetic nanoparticles without proper surface modification. Thus, high surface-area-to-volume ratio of MNPs coated with polyelectrolytes is expected to produce high osmotic pressure [12]. Indeed, it is reported that polyelectrolytecoated MNPs featured an osmotic pressure many folds higher than free polyelectrolyte [13].…”
Section: Introductionmentioning
confidence: 99%